2010
DOI: 10.1016/j.cmet.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Copper Deficiency Activates a Systemic Signaling Mechanism that Communicates with the Copper Acquisition and Storage Organs

Abstract: Copper (Cu) is an essential cofactor for a variety of metabolic functions and the regulation of systemic Cu metabolism is critical to human health. While dietary Cu is absorbed through the intestine, stored in the liver and mobilized into the circulation, systemic Cu homeostasis is poorly understood. We generated mice with a cardiac specific knock out of the Ctr1 Cu transporter, resulting in cardiac Cu deficiency (Ctr1hrt/hrt) and severe cardiomyopathy. Unexpectedly, Ctr1hrt/hrt mice exhibited an increase in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(152 citation statements)
references
References 63 publications
8
144
0
Order By: Relevance
“…4A), and enterocyte Atp7a expression was increased significantly (Fig. 4B), consistent with previous observations made in CuD mice (12). More importantly, cyto-FOX activity was not different in the normal controls compared with the anemic CuD rats (Fig.…”
Section: Fox Activity In Cytosolic Fractions Prepared By Additional Msupporting
confidence: 80%
“…4A), and enterocyte Atp7a expression was increased significantly (Fig. 4B), consistent with previous observations made in CuD mice (12). More importantly, cyto-FOX activity was not different in the normal controls compared with the anemic CuD rats (Fig.…”
Section: Fox Activity In Cytosolic Fractions Prepared By Additional Msupporting
confidence: 80%
“…Interestingly, a similar pattern of heightened serum Cu and reduced kidney and spleen Cu was seen in infections with Coxsackie virus (57), indicating that such fluxes in whole-animal Cu may be common to diverse infectious agents. Elegant studies by Kim et al (58) have demonstrated a cross-tissue communication of Cu status whereby Cu deficiencies in one tissue (e.g., heart) send out a signal to mobilize Cu from other tissues (e.g., liver) to compensate for the metal deficiency (58,59). It is possible that a similar communication occurs during infection to account for the fluxes in tissue and blood stream Cu we report here.…”
Section: Resultsmentioning
confidence: 73%
“…In C. elegans, several neuropeptides are known to mediate intestinal function to regulate metabolism and development (55)(56)(57), although a hepcidin homolog has not been found. Cardiac copper deficiency caused by depletion of the Ctr1 copper importer in the heart induced a significant up-regulation of ATP7A in the intestine of mice, which may lead to increased copper supply into circulation (58). This study suggested that cross-talk may take place between tissue types to coordinate systemic copper homeostasis.…”
Section: Discussionmentioning
confidence: 90%